Pain-induced effects on the pupillary light response under high and low illumination conditions - Kursawe, Michael; Ehrlichmann, Heike; Weber, Walter; Krabbe, Julia; Kraus, Thomas (Frontiers in Neurology, 2024)
Objective. In the present study the impact of two different light intensities on pain modulated pupillary light response (PLR) was investigated. Additionally parasympathetic and sympathetic influences according to pain were aimed to show in PLR parameters as predicted by functional models.Method. Twenty-four participants were finally included in a randomized repeated measures design. Within two test cycles PLR was measured using a dark and a bright light stimulus. Pain was induced using the cold pressor test (CPT) where feet were immersed into ice-water. PLR was measured during baseline and ice-water immersion within each test cycle. The PLR parameters initial diameter (INIT), latency (LAT), amplitude (AMP), and re-dilation time (ReDIL25) were computed and analyzed. Furthermore heartrate (HR) and pain ratings were assessed.Main Results. CPT produced moderate pain level in participants, and PLR parameters were found to be congruent with expected parasympathetic and sympathetic activity. Although stimulus luminance did influence PLR parameters, no interaction with pain exposure was found.Significance. Results show that different aspects of a person experiencing pain modulated through the sympathetic and parasympathetic nervous system are visible in pupillary reaction to light. Light intensity in the range applied within the current study is not relevant concerning the pain related PLR effects.